Evaluation of a Local Anesthesia Simulation Model with Dental Students as Novice Clinicians. Issue 12 (1st December 2015) - Lee, Jessica S.; Graham, Roseanna; Bassiur, Jennifer P.; Lichtenthal, Richard M.
Abstract : The aim of this study was to evaluate the use of a local anesthesia (LA) simulation model in a facilitated small group setting before dental students administered an inferior alveolar nerve block (IANB) for the first time. For this pilot study, 60 dental students transitioning from preclinical to clinical education were randomly assigned to either an experimental group (N=30) that participated in a small group session using the simulation model or a control group (N=30). After administering local anesthesia for the first time, students in both groups were given questionnaires regarding levels of preparedness and confidence when administering an IANB and level of anesthesia effectiveness and pain when receiving an IANB. Students in the experimental group exhibited a positive difference on all six questions regarding preparedness and confidence when administering LA to another student. One of these six questions ("I was prepared in administering local anesthesia for the first time") showed a statistically significant difference (p<0.05). Students who received LA from students who practiced on the simulation model also experienced fewer post‐injection complications one day after receiving the IANB, including a statistically significant reduction in trismus. No statistically significant difference was found in level of effectiveness of the IANB or perceived levels of pain between the two groups. The results of this pilot study suggest that using a local anesthesia simulation model may be beneficial in increasing a dental student's level of comfort prior to administering local anesthesia for the first time.